Das Wesen der alttestamentlichen Prophetie - Jeremias, Jörg (Theologische Literaturzeitung, 2006)
Taken by itself, Old Testament prophecy is a broad-based, generalised Ancient Near Eastern phenomenon. But through the focused selection of specific traditions and the emergence of the prophetic books, it has ondergone a unique development. It is entirely without parallel in two ways: since the exilic period, it has been regarded as fundamental to Israel's relationship to God like the Mosaic tradition. In addition, even before its conclusion in the post-exilic period, it gained canonical dignity as a valid documentation of the will of Yahweh.